Exosomes Derived from Human Umbilical Cord Mesenchymal Stem Cells Relieve Acute Myocardial Ischemic Injury - Yuanyuan Zhao; Xiaoxian Sun; Wenming Cao; Jie Ma; Li Sun; Hui Qian; Wei Zhu; Wenrong Xu (Stem Cells International)
This study is aimed at investigating whether human umbilical cord mesenchymal stem cell- (hucMSC-) derived exosomes (hucMSC-exosomes) have a protective effect on acute myocardial infarction (AMI). Exosomes were characterized under transmission electron microscopy and the particles of exosomes were further examined through nanoparticle tracking analysis. Exosomes (400 μg protein) were intravenously administrated immediately following ligation of the left anterior descending (LAD) coronary artery in rats. Cardiac function was evaluated by echocardiography and apoptotic cells were counted using TUNEL staining. The cardiac fibrosis was assessed using Masson’s trichrome staining. The Ki67 positive cells in ischemic myocardium were determined using immunohistochemistry. The effect of hucMSC-exosomes on blood vessel formation was evaluated through tube formation and migration of human umbilical vein endothelial cells (EA.hy926 cells). The results indicated that ligation of the LAD coronary artery reduced cardiac function and induced cardiomyocyte apoptosis. Administration of hucMSC-exosomes significantly improved cardiac systolic function and reduced cardiac fibrosis. Moreover, hucMSC-exosomes protected myocardial cells from apoptosis and promoted the tube formation and migration of EA.hy926 cells. It is concluded that hucMSC-exosomes improved cardiac systolic function by protecting myocardial cells from apoptosis and promoting angiogenesis. These effects of hucMSC-exosomes might be associated with regulating the expression of Bcl-2 family.